FORMATION OF EXPERIENCE OF CREATIVE ACTIVITY STUDENTS BY MEANS OF CREATIVE TASKS - А.М. Korol (Academy of Cognitive and Natural Sciences, 2004)
The peculiarities of the Creative exercises, which are used at the first level of the formation of the pupils. Creative work at the music lessons are opening in this article.